Peningkatan Absorpsi Cahaya pada Nanostruktur TiO₂ Terdoping Cu dan Ni untuk Aplikasi Pemisahan Air Fotokatalitik - Noni Novianti; Fransischa Ramona; Diana Vanda Wellia; Mulda Muldarisnur (Universitas Andalas, 2025)
This study reports the enhancement of light absorption by TiO₂ nanoparticles when doped with Ni and Cu nanoparticles. Numerical simulations were performed using the boundary element method. The absorbance in the visible region of Ni-doped TiO₂ increases compared to pure TiO₂. The increase in absorbance is accompanied by a shift in the absorption band edge to a longer wavelength (redshift) due to the formation of new energy levels that narrow the band gap. Cu-doped TiO₂ exhibits a more significant increase in absorbance and a wider absorption range. Both dopants decrease the band gap relative to pure TiO₂, with Cu doping producing a greater decrease. Ni and Cu doping enhance the optical response of TiO₂ in the visible region. Cu doping has the most dominant effect in broadening the absorption and lowering the band gap energy. These findings indicate that Ni- and Cu-based dopant engineering is a potential approach to improve the performance of TiO₂-based materials in photocatalytic applications such as hydrogen production by water splitting.